2022
DOI: 10.1039/d2bm00979j
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking the intrinsic vitamin B12 pathway for the oral delivery of nanoparticles, resulting in enhanced in vivo anti-leishmanial activity

Abstract: Surface functionalized vitamin B12 (VB12) biocompatible nanoparticles exploit the well-characterized uptake pathway of VB12, shielding it from enzymatic degradation and inadequate absorption. In this perspective, subsequent to escalated mucus interaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Several studies have further demonstrated the application of vitamin-B12-decorated nanoparticle types for oral insulin delivery. Singh et al recently reported complete cellular uptake of vitamin-B12-coated SLNs for oral delivery of the antileishmanial drug, Amphotericin B, with enhanced efficacy . In the follow-up study, the internalization mechanisms of the conjugate were investigated, with researchers finding that uptake occurred via clathrin-mediated pathways, bypassing P-glycoprotein efflux …”
Section: Nanoparticle Uptake: Taking Advantage Of Receptor-mediated E...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have further demonstrated the application of vitamin-B12-decorated nanoparticle types for oral insulin delivery. Singh et al recently reported complete cellular uptake of vitamin-B12-coated SLNs for oral delivery of the antileishmanial drug, Amphotericin B, with enhanced efficacy . In the follow-up study, the internalization mechanisms of the conjugate were investigated, with researchers finding that uptake occurred via clathrin-mediated pathways, bypassing P-glycoprotein efflux …”
Section: Nanoparticle Uptake: Taking Advantage Of Receptor-mediated E...mentioning
confidence: 99%
“…138 In the follow-up study, the internalization mechanisms of the conjugate were investigated, with researchers finding that uptake occurred via clathrin-mediated pathways, bypassing P-glycoprotein efflux. 139 The neonatal Fc receptor (FcRn) is present on numerous cells in all stages of life with various functions, including the transport, retention, and recycling of materials. 140 In the human intestine, FcRn recognizes the Fc region of antibodies and binds with high affinity under mildly acidic conditions (pH 6−6.5), followed by transcytosis across the gut epithelium.…”
Section: Nanoparticle Uptake: Taking Advantage Of Receptor-mediated E...mentioning
confidence: 99%
“…This therapeutic approach did not induce cellular toxicity or severe disruption in membrane viscoelasticity. The formulation's consistent mucus retention ability significantly impacted its systemic absorption and subsequent bioavailability [127]. The other research group utilized sonication to fabricate nano-VB 12 (120-180 nm) and nano-penicillin (70 nm) with the enhanced bio-functional effects like antimicrobial activity [128].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The physiological barriers in the small intestine include the mucus layer, intestinal epithelial cells (IECs), and submucosal lamina propria, which effectively resist invasion from xenobiotics. , Nanocarriers have been designed to escape mucus capture and enable transport across IECs and submucosal lamina propria to improve absorption. , Although hydrophilicity and electroneutrality endowed the nanocarriers with high permeability across the mucus layer, the hydrophilic surface significantly reduced interactions between the nanocarriers and IECs, resulting in poor epithelial cell transportation . Vitamin B12 (VB 12 ) has been shown to bind with intrinsic factor (IF) and enable transport across the intestinal epithelium via IF receptor-mediated cellular uptake at the ileum, suggesting that this could be used as a ligand to improve oral bioavailability. The surface modification of VB 12 has been verified to increase the cellular uptake of nanoparticles, liposomes, and polymeric micelles by IECs and thus improve the bioavailability of small molecules and peptides after oral administration. Moreover, the lack of VB 1 2 induces the increment in unmetabolized homocysteine that promotes local inflammation at the endothelial layer, and supplementation of VB 1 2 , which is beneficial to the decomposition of homocysteine, prevents the progression of AS . Collectively, modification of the surface of nanoemulsion with VB 1 2 may “kill two birds with one stone” to enhance transportation across the epithelial layer and stabilize atherosclerotic plaques.…”
mentioning
confidence: 99%